Respostas
respondido por:
1
Olá!!!
Resolução!!!
x² - 6x + 1 = 0
a = 1, b = - 6, c = 1
∆ = b² - 4ac
∆ = ( - 6 )² - 4 • 1 • 1
∆ = 36 - 4
∆ = 32
x = - b ± √∆ / 2a
x = - ( - 6 ) ± √32 / 2 • 1
32 | 2
16 | 2
8 | 2
4 | 2
2 | 2
1
√2² • 2² • 2 = √32
√4² • 2 = √32
4 • √2 = √32
4√2 = √32
x = 6 ± 4√2 / 2
x' = 6 + 4√2
x" = 6 - 4√2
S = { 6 - 4√2, 6 + 4√2 }
Espero ter ajudado!!,
Resolução!!!
x² - 6x + 1 = 0
a = 1, b = - 6, c = 1
∆ = b² - 4ac
∆ = ( - 6 )² - 4 • 1 • 1
∆ = 36 - 4
∆ = 32
x = - b ± √∆ / 2a
x = - ( - 6 ) ± √32 / 2 • 1
32 | 2
16 | 2
8 | 2
4 | 2
2 | 2
1
√2² • 2² • 2 = √32
√4² • 2 = √32
4 • √2 = √32
4√2 = √32
x = 6 ± 4√2 / 2
x' = 6 + 4√2
x" = 6 - 4√2
S = { 6 - 4√2, 6 + 4√2 }
Espero ter ajudado!!,
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás